2014
DOI: 10.1136/bjophthalmol-2014-305223
|View full text |Cite
|
Sign up to set email alerts
|

The Spaeth/Richman contrast sensitivity test (SPARCS): design, reproducibility and ability to identify patients with glaucoma

Abstract: NCT01300949.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 22 publications
4
50
1
Order By: Relevance
“…Since classical glaucomatous visual field loss is usually detected first in the periphery, often as an arcuate scotoma occurring in the superior or inferior hemifield within 20°of the fovea, attempts were subsequently made to correlate the peripheral visual field loss with contrast sensitivity measurements [6]. Richman et al [7] found that contrast sensitivity loss correlated more closely and strongly to glaucomatous damage than binocular visual field loss in patients with glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Since classical glaucomatous visual field loss is usually detected first in the periphery, often as an arcuate scotoma occurring in the superior or inferior hemifield within 20°of the fovea, attempts were subsequently made to correlate the peripheral visual field loss with contrast sensitivity measurements [6]. Richman et al [7] found that contrast sensitivity loss correlated more closely and strongly to glaucomatous damage than binocular visual field loss in patients with glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with some former studies, we found a relatively lower ICC for PR, perhaps because we only had two test repetitions and a relatively small sample size. We have already reported a very close correlation between the ICCs of SPARCS and PR 17. A Bland–Altman plot showed that the mean difference in measurements was close to 0 for PR and SPARCS, although with different scales.…”
Section: Discussionmentioning
confidence: 53%
“…Key features of SPARCS include independence from optotypes, simplicity of testing, ability to test various areas of the visual field and global accessibility via the internet, only requiring low-cost hardware, no-cost software (standard web browsers). The test has been shown to be highly reproducible and of clinical value in finding patients with glaucoma 17. In the present study, we consider the ability of SPARCS to assess CS in individuals with different refractive errors.…”
Section: Introductionmentioning
confidence: 99%
“…SPARCS has been found to distinguish between glaucoma patients, glaucoma-suspects, and controls and be correlated with the degree of damage to the visual field and optic nerve in these subjects. 11 A recent study has found SPARCS to be useful for assessing CS in patients with age-related macular degeneration. 19 SPARCS has certain limitations including subject fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The testing strategy uses a staircase method with reversals as described by Richman et al 11 In the beginning, correct responses allow the subject to advance 4 levels until an incorrect response is made. Then, the algorithm presents a contrast level that is 2 levels easier.…”
Section: Spaeth/richman Contrast Sensitivity Test (Sparcs)mentioning
confidence: 99%